THE INFLUENCE OF PROBLEM SOLVING TYPE TEACHER TEACHING VARIATIONS ON LEARNING OUTCOMES OF CLASS XI IPS STUDENTS OF STATE 16 BONE - Samsidar; Haeril; Sahiruddin (CV. Fahr Publishing, 2024)
This research aims to determine the effect of teacher teaching variations in the type of problem solving on the learning outcomes of Class XI IPS students at SMA Negeri 16 Bone. This research is a post facto research. The variables of this research are student learning outcomes, Teacher Teaching Variations Type Problem Solving. The population in this study was 32 students of class XI IPS 1 SMA Negeri 16 Bone. The data collection technique uses a questionnaire. The analysis method uses the Rehabilitation Test, Reliability Test, and t Test. From the results of the research, it was concluded that, the learning outcomes of class and H1 is accepted. Indicators of the criteria for completeness of student learning outcomes determined by researchers, it can be concluded that learning outcomes after implementing the Problem Solving learning model have increased compared to during the Pre Test, which means that they have met the criteria for completeness of learning outcomes, namely 84.375% ≥ 70%.